Differences in rhizospheric microbial communities between cultivated and wild endangered Glyptostrobus pensilis - Yang, Xiaojuan; Deng, Biyu; Lu, Shiyi; Wang, Cong; Liang, Yongyan; Liu, Shinan (Frontiers in Microbiology, 2025)
Glyptostrobus pensilis is an endangered species belonging to the Cupressaceae family. The comprehensive examination of soil characteristics and rhizosphere microbial communities is vital for conservation efforts, as it provides insights into the necessary environmental conditions for safeguarding and ensuring the viability of rare and endangered species. In this study, the diversity and composition of bacterial and fungal communities were compared in the roots and rhizosphere soils of cultivated and wild G. pensilis in Guangxi, China. The results revealed that, at the phylum level, the rhizosphere of cultivated G. pensilis was significantly enriched with Verrucomicrobiota, Acidobacteriota, Glomeromycota, and Chloroflexi, while wild G. pensilis was significantly enriched with Planctomycetota, Basidiomycota, and Ascomycota. Symbiotic network analysis indicated that the bacterial network in the cultivated G. pensilis rhizosphere had higher edge values, average degree, clustering coefficient, and network density, while the fungal network in the wild G. pensilis rhizosphere had higher node values, edge values, average degree, and clustering coefficient. Moreover, functional prediction results suggested that bacteria in cultivated G. pensilis showed higher metabolic activity, with fungi primarily acted as saprotrophs and symbionts. In contrast, bacteria in wild G. pensilis displayed lower metabolic activity, with fungi predominantly functioning as saprotrophs. The analysis linking rhizospheric microbial diversity to soil environmental factors showed a closer association for the wild G. pensilis microbial community, suggesting a stronger influence of soil environmental factors. The Random Forest (RF) highlighted that the total phosphorus and total potassium levels were key influencing factors for rhizospheric microbes in cultivated G. pensilis, while available potassium levels were crucial for those in wild G. pensilis. These differences underscore the significant strategies for G. pensilis in adapting to different habitats, which may be intricately linked to land management practices and soil environmental factors. Among these, phosphorus and potassium are significantly associated with the rhizosphere microorganisms of G. pensilis. Therefore, continuous monitoring of nutrient availability and regular supplementation of phosphorus and potassium fertilizers in the rhizosphere are recommended during the cultivation and ex-situ conservation of G. pensilis.